Monotonous Driving Environment along Highway and Driver Behaviour in Malaysia: A Review - Zainon, M.; Zaly Shah, M.; Chiroma, M.A.; Kafi, M.A. (Journal of the Society of Automotive Engineers Malaysia, 2021)
Driver alertness, behaviour, and performance are central aspects of road traffic safety to achieve sustainable mobility. In addition, the type of environment where mobility occurs tend to affect drivers. Typically, monotonous stretches along highway deteriorate drivers’ vigilance thus leading to fatigue, drowsiness, and even crashes. Based on extensive review of related literature, this paper shall present the various issues of monotonous driving environment, countermeasures, as well as related research in Malaysia, aside from highway landscaping and other fatigue related road safety issues. Despite the significant amount of research on such issues, due to the current development trend and the highly motorised nature of Malaysia, there is need for more robust research especially in terms of countermeasure improvement and appraisal as well as development of monotony effect indices.